Ecology and breeding biology of the pond heron, Ardeola grayii (Sykes, 1832) and its conservation aspects - Jaman, M Firoj; Hoque, Md Nazmul; Sarker, Noor Jahan; Rahman, Md Saidur (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Studies on ecology and breeding biology of the pond heron, Ardeola grayii was conducted from January to June, 2010 in Kalairpur Assim Union, Fulbaria under Mymensingh district. The breeding season of this bird ranged from February to June. The peak period for nesting was March. The pond heron choose the nesting site surrounding the human settlements near the pond and other water bodies. This species took 7 to 14 days to complete nest with an average of 10.8 days. The height of nest varied from 5.2 m to 10.9 m with an average of 7.82 m. The main nesting trees were bamboo (Bambusa longispiculata) and mango (Mangifera indica). Nesting materials were chiefly small sticks of mango, tamarind (Tamarindus indica), bel (Aegle marmelos) and leaves of bamboos. The clutch size varied from 3 to 4 eggs with an average of 3.7 eggs. The incubation period varied from 19 to 23 days with an average of 20.73 days. The hatching success was 90% in relation to the number of eggs laid. The fledging period of young varied from 25 to 29 days with an average of 26.73 days. Young individuals left the nest after 3 to 4 weeks. Results of this study indicate that the pond heron can breed successfully for their survival if indigenous plants trees are available to build their nest. So Government should make immediately an integrated conservation plan to protect this bird with the co-operation of national and international organizations. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15325 J. Asiat. Soc. Bangladesh, Sci. 38(1): 99-109, June 2012